Seven doors to Islam: spirituality and the religious life of Muslims - Renard, John (University of California Press, 1996)
Reveals the religious worldview and spiritual tradition of the world's one billion Muslims. Spanning the breadth of Islamic civilization from Morocco to Indonesia, this book demonstrates how Muslims have used the literary and visual arts in all their richness and diversity to communicate religious values. Each of the seven chapters opens a "door" that leads progressively closer to the very heart of Islam, from the foundational revelation in the Qur'an to the transcendent experience of the Sufi mystics. However, unlike most studies of Islam, which see spirituality as the concern of a minority of mystical seekers, this book demonstrates its central role in every aspect of the Islamic tradition.--From publisher description